Mexicans in the Making of America - NEIL FOLEY (Harvard University Press, 2014)
Some readers might wonder why a person with a non- Latino name like â€œNeil Foleyâ€ would feel the urge or the need to write about Mexican Americans and Mexican immigrants. It never occurred to me, growing up in the suburbs of Washington, DC, in the 1950s and 1960s, that I was any different from the kids I went to parochial school with. We were all â€œwhiteâ€â€” no African Americans or other Latinos attended my elementary school. Most blacks lived in the capital city, as did the tiny Latino community, mostly Central Americans who settled around 18th and Columbia Road in a neighborhood called Adams Morgan. In those days the words â€œLatinosâ€ and â€œHispanicsâ€ were not much in use. Th at came later, in the 1970s, about the same time that I began to ponder the challenges our immigrant grandparents faced in making the journey to the United States. My father, Raymond Patrick Foley, was the son of impoverished Irish immigrants from County Kerry, Ireland. He was the youn gest of seven children born in Brockton, Massachusetts. His mother, Julia Sheehan Foley, died shortly aft er he was born. His church gave him a scholarship to attend Boston College, where he studied Spanish and subsequently made a living as a Spanish translator for the FBI and the Department of Justice. My mother, Maria Lilia Trejo, one of nine children, was the daughter of Mexican immigrants who crossed the border into New Mexico before it was illegal to cross without papers. Today she would be called an â€œanchor baby.â€ Th ey met during World War II. Like my father, she was a devout Catholic, but practiced the rituals and rhythms of â€œfolk Catholicismâ€ that she was brought up with. Her devotion to the Virgin Mary included our praying the rosary every day aft er dinner during the month of May while our neighborhood friends played ball in the street. At home I listened to my motherâ€™s scratchy rec ords of Mexican ranchera music and grew up thinking her enchiladas, tacos, tamales, frijoles, and sopapillas were American food, which of course they are. But not everyone thought so at the time. Th is was long before Taco Bell spread from California to the East Coast.